Lessons From Ceramic Petrography: A Case of Technological Transfer During the Transition From Late to Inca Periods in Northwestern Argentina, Southern Andes - De La Fuente Guillermo A.; Vera Sergio D.; Rasmussen Kaare L.; Martínez Carricondo Marina G. (Open Archaeology)
Pottery production during the Late Period (circa 950–1450 AD) in Northwestern Argentina (NWA) was characterized by conservative and household-based production, primarily utilizing local raw materials. During this era, potters engaged in a specific material practice involving the addition of grog (or crushed pottery fragments) to certain ceramic vessels such as infant funerary urns and bowls. This practice was linked to a distinct animistic worldview that shaped how people perceived and connected with various materials and nature. In contrast, Inca pottery (circa 1450–1532 AD) exhibited a high degree of standardization in terms of form and size. It was produced in a centralized manner across the entire territory, mainly through the labor system known as “mita” at various geographical workshops in the Andean region. This article aims to evaluate and discuss how potters during Inca times borrowed the practice of using grog at NWA. It seems to have been a deliberate technological choice adopted by these potters, possibly influenced by practices from the Late Period potters.